Pengalaman Akademik Internasional Mahasiswa Ilmu al-Qur'an dan Tafsir dalam Program Student Mobility Malaysia - Eka Rahmawati; Ulil Abshar. Hs (ANWARUL, 2026)
Although international student mobility programs have been widely implemented by various higher education institutions, studies that specifically discuss their contribution to strengthening perspectives in Qur’anic Studies and Exegesis as well as developing students’ academic and cross-cultural competencies remain relatively limited. This article aims to explore the international academic experiences of students in the Qur’anic Studies and Exegesis Study Program through the International Student Mobility Program held at Universiti Sains Islam Malaysia and Universiti Kebangsaan Malaysia. This study used a qualitative approach with a reflective case study design, involving one student participant in the program as the main informant. Data were collected through participatory observation, activity documentation, and reflections on experiences during the implementation of the program, then analyzed descriptively and qualitatively by examining the academic, social, and cultural experiences gained. The results showed that the international mobility program contributed to broadening students’ academic insights through learning tajwid, hifz al-Qur’an, the Braille Qur’an, international seminars, academic competitions, and interactions with the higher education environment in Malaysia. This program also developed cross-cultural communication skills, social adaptation, public speaking, teamwork, and understanding of inclusive and technology-based Islamic education practices. The experience of facing social, academic, and technical challenges also shaped students’ maturity, responsibility, and problem-solving abilities. The conclusion of this study affirms that International Student Mobility is a strategic means of strengthening students’ academic capacity, Islamic insight, and cross-cultural competencies. The implications of this study provide theoretical contributions to the development of studies on the internationalization of Islamic education and practical contributions for higher education institutions in designing international programs oriented toward strengthening students’ academic and global competencies.